Does the impact of a multidomain intensive lifestyle intervention on cognitive function depend on baseline frailty?: Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Simpson, Felicia R; Carmichael, Owen T; Hayden, Kathleen M; Hugenschmidt, Christina; McCaffery, Jeanne; Ojeranti, Daniel; Pajewski, Nicholas M; Roman‐Ashby, Glorian; Yasar, Sevil; Espeland, Mark A
Abstract: Background: Type 2 diabetes and obesity, separately and in combination, are known to accelerate cognitive decline, increasing one's risk of dementia. While lifestyle interventions may be expected to mitigate cognitive decline and dementia risk through multiple pathways, the Action for Health in Diabetes (Look AHEAD) randomized controlled clinical trial found no overall benefit from 10 years of multidomain intensive lifestyle intervention (ILI) compared to diabetes support and education (DSE). However, there was some evidence that the impact of the intervention on cognitive outcomes was heterogeneous, ranging from benefit for individuals with lower body mass index and no history of cardiovascular disease to harm for the heaviest individuals with a history of cardiovascular disease history. We hypothesized that the impact of the intervention on cognitive function may vary among individuals grouped according to a geroscience construct for biological aging, the Rockwood deficit accumulation frailty index (FI). Method: A standardized battery of cognitive function tests was administered to 3, 708 Look AHEAD participants, 10‐13 years after they had been randomized to 10 years of ILI or the DSE control condition. Participants, who were aged 45‐76 at baseline, were grouped according to tertiles of a 38‐item FI calculated from baseline characteristics. Analyses of covariance with interaction terms were used to assess the consistency of any intervention effects among FI tertiles. Result: The median FI score was 0.20 at baseline, with 12% classified as frail (FI>0.21). Greater baseline FI was associated with poorer cognitive function in domains related to attention, processing speed, and executive function (all p< 0.01), but not memory. Assignment to ILI was not associated with better cognitive functioning in any domain, and this finding was consistent across FI tertiles and inverse probability weighted analyses. Conclusion: A 10‐year multidomain intensive lifestyle intervention that produced marked and sustained improvements in weight and physical activity did not provide cognitive benefits regardless of frailty at study entry. Although intervention effects on cognitive function were heterogeneous across the range of obesity and cardiovascular disease history, this heterogeneity was not evident across the range of deficit accumulation seen in the cohort.